Flexural creep response of honeycomb sandwich pultruded GFRP composite cross-arm: obtaining full-scale viscoelastic moduli and creep coefficients - Amir, Abd Latif; Ishak, Mohammad Ridzwan; Yidris, Noorfaizal; Mohd Zuhri, Mohamed Yusoff (Elsevier, 2024)
The application of pultruded glass fibre-reinforced polymer composites (PGFRPC) as a replacement material for conventional wooden cross-arm in high transmission towers is relatively new. Although there are several studies on enhancement of the cross-arm structure, there is still a lack of study on the elastic properties of a full-scale PGFRPC cross-arm enhanced with honeycomb sandwich structure. To full-fill the gap, this paper describes an experimental methodology used to obtain the elastic properties of the cross-arm using a three-point bending (3-PB) flexural test by following ASTM D790 standard for deflection behaviour and flexural creep response. The investigation involved several cross-arm members subjected to loading across different span lengths by propose two methods in order to measure the effective cross-arm member section flexural modulus (Ec) and shear modulus (Gc). The creep behaviour of the panels was successfully modeled using Findley's power law, confirming the ability of this empirical approach to simulate the viscoelastic response of the cross-arm. Next predictions were made for up to 50 years of service and the results shows the elastic modulus reduction for the enhanced cross-arm with the honeycomb sandwich structure was approximately reduce to 70 compare with existing cross-arm which reduce almost 75 at 50 years of application. The enhanced cross-arm exhibited lower deflection and better creep resistance and increased the bending strength of the cross-arm as well as extended its potential lifespan. Predictions indicated that the enhanced cross-arm maintained better mechanical properties over time compared to the existing one.